Konten Kekerasan Simbolik pada Wacana Virtual Youtuber Indonesia - Azhar, Ghina Zoraya; Saidi, Acep Iwan; Sulistyaningtyas, Tri; Waskita, Dana (PANGGUNG, 2025)
This study examines the usage of symbolic violence in the discourse of the live-stream of an Indonesian virtual youtuber (vtuber), Kanna Tamachi, using qualitative approach and post-structural discourse analysis (DA) method. The focus of this study is on textual elements of language violence used by the Vtuber and their relation to viewer in their social context. This study aims to examine the relations between the usage of symbolic violence and the viewer’s reception. Through the DA method, the linguistic elements of the Vtuber are specifically studied in relation to the language violence content. However, the violent language is studied in the context of local culture, the meanings of which are relevant to values, norms, and characteristics of the local culture. The result of this study confirms that the language violence used by the Vtuber in the context of local culture in East Java is not always negative or destructive. Instead, it provides positive and constructive value by attracting and entertaining viewers, and giving them senses of familiarity and closeness. It also provides economic value to the Vtuber through their status as commodities.